2023
DOI: 10.1177/10731911231161779
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Latent Structure of Executive Function in the Delis–Kaplan Executive Function System Using Cattell–Horn–Carroll Theory

Abstract: Objective: To replicate a seven-factor model previously reported for the Delis–Kaplan Executive Function System (D-KEFS). Method: This study used the D-KEFS standardization sample including 1,750 non-clinical participants. Several seven-factor models previously reported for the D-KEFS were re-evaluated using confirmatory factor analysis (CFA). Previously published bi-factor models were also tested. These models were compared with a three-factor a priori model based on Cattell–Horn–Carroll (CHC) theory. Measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Design fluency and verbal fluency tests involve several EF-components, but are mainly considered to test for cognitive flexibility ( Diamond, 2013 ). Latent structure analyses have shown that both tests include factors (named fluency and shifting) that are relatively independent from other EF component such as inhibition, processing speed and fluid reasoning ( Karr et al, 2019 ; Furey et al, 2024 ). While VF1-2 and DF1-2 are considered to have a larger fluency component, VF3 and DF3 are considered to have a larger switching component (see further Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%
“…Design fluency and verbal fluency tests involve several EF-components, but are mainly considered to test for cognitive flexibility ( Diamond, 2013 ). Latent structure analyses have shown that both tests include factors (named fluency and shifting) that are relatively independent from other EF component such as inhibition, processing speed and fluid reasoning ( Karr et al, 2019 ; Furey et al, 2024 ). While VF1-2 and DF1-2 are considered to have a larger fluency component, VF3 and DF3 are considered to have a larger switching component (see further Supplementary Methods ).…”
Section: Methodsmentioning
confidence: 99%
“…The Cattell-Horn-Carroll (CHC) theory of abilities (see Flanagan & Dixon, 2014;Schneider & McGrew, 2012a, 2012b, for more detail) is a comprehensive model of human cognitive abilities that has been updated over the past few years (see Euler, Vehar, &Guevare, 2023, andMcGrew, 2023, for detail), and applied in many areas of studies, to list a few, autism spectrum disorder (Chua & Xie, 2022), executive functions (Furey et al, 2024), figurative language comprehension (Biesok et al, 2024), sensory abilities/disabilities (Liu & Xie, 2023), and CHC-based validation of a digital cognitive test battery (Vermeent et al, 2020).…”
Section: Introductionmentioning
confidence: 99%